2016
DOI: 10.1111/apt.13703
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: patient‐reported outcome measures in coeliac disease for regulatory submissions

Abstract: While we did not find PROMs that currently meet the stated expectations of the FDA for regulatory purposes, four PROMs (CeD-GSRS, PGWB, CDSD and CeD-PRO) appear to contain appropriate content and with modest additional validation work could meet scientific standards for valid and sensitive measures of disease and treatment outcome. Specifically, what is needed for these instruments is an understanding of how sensitive they are to real changes in-patient condition, how stable they are over a period of time when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 102 publications
(107 reference statements)
1
32
0
2
Order By: Relevance
“…The poor correlation of histology and serology with symptoms has highlighted the need for suitable tests to monitor relevant clinical responses to gluten in trials of novel therapies intended for coeliac disease patients on gluten‐free diet . Symptoms measured by patient‐reported outcome instruments are increasingly used as efficacy endpoints in clinical trials .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The poor correlation of histology and serology with symptoms has highlighted the need for suitable tests to monitor relevant clinical responses to gluten in trials of novel therapies intended for coeliac disease patients on gluten‐free diet . Symptoms measured by patient‐reported outcome instruments are increasingly used as efficacy endpoints in clinical trials .…”
Section: Discussionmentioning
confidence: 99%
“…The poor correlation of histology and serology with symptoms has highlighted the need for suitable tests to monitor relevant clinical responses to gluten in trials of novel therapies intended for coeliac disease patients on gluten-free diet. 4,5,29 Symptoms measured by patient-reported outcome instruments are increasingly used as efficacy endpoints in clinical trials. 30 Here, we show that standardised oral gluten challenge, combined with cytokine assessment and patient-reported outcomes adapted for hourly rating (as described for the first time in this study), is well suited to monitoring the effects of gluten in coeliac disease patients.…”
Section: Discussionmentioning
confidence: 99%
“…A key finding in this study was that only coeliac disease-specific PROs met all of our stringent evaluative criteria 15. A recently published systematic review reported four appropriate PROs for use in coeliac disease trials 51. It should be noted, however, that only two of these, the CDSD and the CeD-PRO, are coeliac disease-specific PROs that were developed according to the FDA SEALD criteria and can thus be used for labelling purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Some coeliac‐specific measures have been developed, for example, the Coeliac Disease Questionnaire (CDQ) and the Coeliac Disease Quality of Life Survey (CD‐QOL) . A systematic review identified four candidate coeliac‐specific PROMs for use in clinical trials and concluded that none of these meet the standards of the US Food and Drug Administration . Another systematic review focused on patient‐reported symptom scores and identified two coeliac disease indices that have been approved by the US Food and Drug Administration.…”
Section: Introductionmentioning
confidence: 99%